2015
DOI: 10.11604/pamj.2015.21.120.7079
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors for chronic kidney disease among adults in a university community in southern Nigeria

Abstract: IntroductionThe rising prevalence of chronic kidney disease (CKD) remains a global public health challenge particularly in developing countries, including our local environment, where subjects with the disease present late and may already be in need of renal replacement therapy. Early detection of modifiable risk factors of CKD is a plausible strategy to reduce its prevalence and burden. The 2014 World Kidney Day (WKD) exercise provided a veritable opportunity to identify CKD risk factors among adult Nigerians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 22 publications
10
30
0
Order By: Relevance
“…Similarly, BMI was also found to be higher in female than male in this study which is consistent with the findings of Nalado et al (2012) among civil servants in Kano and that of Gallagher et al (1996). However, Wachukwu et al (2015) reported contrary in the southern part of Nigeria that males are higher in BMI than females; this may be connected with the differences in the socio-demographic factors between the regions. Body mass index and prevalence of obesity with kidney disease were found to be higher than in those without the disease in both genders (Nomura, et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, BMI was also found to be higher in female than male in this study which is consistent with the findings of Nalado et al (2012) among civil servants in Kano and that of Gallagher et al (1996). However, Wachukwu et al (2015) reported contrary in the southern part of Nigeria that males are higher in BMI than females; this may be connected with the differences in the socio-demographic factors between the regions. Body mass index and prevalence of obesity with kidney disease were found to be higher than in those without the disease in both genders (Nomura, et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, indicated that young people like university students were also at high risk of developing CKD. [13] From our review, there has not been a study conducted on level of knowledge and preventive practices of risk factors of CKD in Rwanda. The aim of this study was to assess the knowledge of risk factors and preventive practices of CKD among university students at one selected University in Rwanda.…”
Section: Introductionmentioning
confidence: 95%
“…In 2015, the American Food & Drug Administration (FDA) strengthened its warning that NSAID use increased the chances of developing heart attacks or strokes even following short term use 15. This is noteworthy especially within the Nigerian setting, where an increasing number of adults have one or more cardiovascular disease (CVD) risk factors 16,17,18. A related concern is the renal damage associated with these agents especially when they are used in combination with other nephrotoxic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…A related concern is the renal damage associated with these agents especially when they are used in combination with other nephrotoxic drugs. Kidney disease is on the rise worldwide due to a variety of factors, however the prognosis of patients with this condition in third world settings like Nigeria is remarkably worse 18. Other side effects of NSAID misuse can include gastrointestinal (GI) side effects and bleeding.…”
Section: Introductionmentioning
confidence: 99%